On Some Integral Transformations and Their Application to the Solution of Boundary-Value Problems in Mathematical Physics - Popov, G. Ya. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We obtain a formula for the expansion of an arbitrary function in a series in the eigenfunctions of the Sturm–Liouville boundary-value problem for the differential equation of cone functions. On the basis of this result, we derive a series of integral transformations (including well-known ones) and inversion formulas for them. We apply these formulas to the solution of initial boundary-value problems in the theory of heat conduction for circular hollow cones truncated by spherical surfaces.